2011
DOI: 10.1115/1.4004548
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Irradiance Mapping of a Low Cost Solar Simulator for Indoor Testing of Solar Collector

Abstract: The fabrication and testing of a solar simulator for indoor testing of solar collector are described. Consisting of Philips 500 W halogen lamps with built-in reflector, which are arranged at 30 cm apart, the system covers a test area suitable for a solar collector of size 120 cm by 53 cm. The height of the lamps above the solar collector under test is set to 160 cm. Measurement of the uniformity of the irradiance over the test area has been made. Four sets of irradiance mapping were performed at 466, 580, 686,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…In the research published by several researchers [17,32e35] the minimum characteristics or standards as listed in ASHRAE were followed in their research, tungsten halogen lamps were employed for the solar simulator and concluded as sufficient and reliable for the indoor collector testing. While, a variety of types of lamps have been suggested, in this study, by referring to the work of [Othman et al [21], Garg, et al [32], Hussain, et al [33], Agrawal, et al [34]], a low-cost simulator which consists of a 3-phase array of 30 quartz-halogen tungsten lamps of Philips Plusline Small Double-Ended Linear Lamps of 500 W each installed on a lamp casing with a reflector arranged on a steel support structure with (1.4 m  1.4 m) in size was fabricated for the collector indoor testing. The simulator is capable to produce solar intensities of up to 800 W/m 2 .…”
Section: Experimental Studymentioning
confidence: 97%
See 1 more Smart Citation
“…In the research published by several researchers [17,32e35] the minimum characteristics or standards as listed in ASHRAE were followed in their research, tungsten halogen lamps were employed for the solar simulator and concluded as sufficient and reliable for the indoor collector testing. While, a variety of types of lamps have been suggested, in this study, by referring to the work of [Othman et al [21], Garg, et al [32], Hussain, et al [33], Agrawal, et al [34]], a low-cost simulator which consists of a 3-phase array of 30 quartz-halogen tungsten lamps of Philips Plusline Small Double-Ended Linear Lamps of 500 W each installed on a lamp casing with a reflector arranged on a steel support structure with (1.4 m  1.4 m) in size was fabricated for the collector indoor testing. The simulator is capable to produce solar intensities of up to 800 W/m 2 .…”
Section: Experimental Studymentioning
confidence: 97%
“…For the collector indoor testing, the ideal solar simulator would consist of lamps in which the spectral distribution resembles the spectral distribution of the sunlight. However, due to economical and physical constraint, this is impossible to achieve [33]. In the research published by several researchers [17,32e35] the minimum characteristics or standards as listed in ASHRAE were followed in their research, tungsten halogen lamps were employed for the solar simulator and concluded as sufficient and reliable for the indoor collector testing.…”
Section: Experimental Studymentioning
confidence: 99%
“…Requirements considering sun simulators are found in the American Standard for Testing and Materials (ASTM) E972. According to this standard, sun simulators can be classified by three main aspects into different classes, however, any sun simulator must be able to provide the average surface light intensity (AM 1.5) with a maximal 1,000 W/m 2 value [1][2][3][4]25].…”
Section: Astm E972 Standardmentioning
confidence: 99%
“…Sun simulators can then be classified into class A, B or C based on the previously mentioned three aspects. The requirements of the three groups are summarized in Table 1 [1][2][3][4]25]. The stricter requirements of class A and B sun simulators carry a higher cost and an increased time of development, hence taking the feasibility into account, we set the development of an ASTM E972 standardized, class C sun simulator as the main objective for our research and development project.…”
Section: Astm E972 Standardmentioning
confidence: 99%
“…The performance of the PV/T solar collector had been tested indoor using a laboratory fabricated solar simulator. The solar simulator had been tested in terms of its irradiance repeatability and uniformity (Hussain 2011). The test area of the solar simulator is 120 cm x 53 cm suitable for the size of the solar collector that is tested under the simulator.…”
Section: Experimental Set-upmentioning
confidence: 99%